Finding Your Place: Assessing Diversity, Equity, and Inclusion in an Academic Library - Thomas, Khaleedah; Houlihan, Meggan (Evidence Based Library and Information Practice, 2025)
Objective – An exploratory study was conducted to identify the key factors that influence students’ perceptions of a sense of belonging in an academic library, focusing particularly on gaining insight into the perspectives of students from historically marginalized communities.Methods – Participants were administered an online survey comprising 18 multiple-choice, Likert-type, and open-ended questions. The survey was active for three weeks during March and April 2022. Effect sizes were calculated using Pearson point-biserial correlation statistics. Qualitative results were coded using thematic analysis.Results – An analysis of the quantitative data revealed that students who identified as non-binary/queer/gender non-conforming, identified as a person of color, or identified as a person with a disability were less likely to find the library as inclusive. They were also more likely to report incidents of microaggression, bias, or discrimination. An analysis of the qualitative data revealed several key factors influencing perceptions of inclusiveness, including space, collections, displays, art, technology, programming, marketing, staff, and wayfinding.Conclusion – These mixed findings suggest that while the majority of students perceive the library environment as inclusive, further efforts are needed to establish a truly inclusive and safe space for students from historically marginalized communities.